Measuring Occupational Self-Efficacy: A Culinary Students' Cooking Performance Perspective - Tuatul Mahfud; Mutiara Nugraheni; Pardjono Pardjono; Badraningsih Lastariwati (Faculty of Engineering, Universitas Negeri Yogyakarta, 2021)
Occupational self-efficacy is believed to be an essential factor for optimizing mastery of cooking competencies for culinary students. Although there have been many studies examining the importance of self-efficacy, there are still limited studies that discuss how to measure the self-efficacy of cooking abilities for culinary vocational students. This study aims to develop and test the validity of the self-efficacy cooking skills questionnaire. This study involved 329 culinary students in the Special Region of Yogyakarta, Indonesia. Data analysis uses Confirmatory Factor Analysis (CFA) to test the validity and reliability. The results of the study revealed that the occupational self-efficacy of cooking performance could be explained by four indicators, namely the enactive experience, model experience, social persuasion, and emotional conditions. This questionnaire has 16 items consisting of 4 items in each indicator. The results of this study have implications for industry and education practitioners to evaluate the achievement of mastery of students 'and chefs' cooking skills.